Study Regarding the Perception of Small Farmers from the South- East of Romania on Social Agricultural Cooperatives - Virlanuta, Florina Oana; Moisescu, Florentina; Manea, Daniela Ludmila (European Journal of Sustainable Development, 2017)
Abstract Social economy suggests new, innovative solutions to certain social, economic or environmental problems of communities in order to meet the needs expressed by community members, which are insufficiently covered or ignored by the public or the private sector. The domain represents a priority both at the national and at the European level for the period 2014 – 2020, being a research topic for the academic environment and the subject of a great number of scientific conferences and research studies. The study below presents the original research performed by the authors in order to determine the social agricultural cooperative acceptability degree among the farmers from the south-east of Romania. The first stage of the research strategy materialised in various documentation activities regarding the draw-up of a questionnaire and finished with the completion of the questionnaire and of the computer-based methodology used for its processing. The second stage involved the design of the sample structure and size and the processing methodology. In the third stage, we put forward the working hypotheses and we identified the connection degree between the variables that constituted the basis for making the hypotheses. Keywords: social economy, social agricultural cooperative, sustainable development